1800 Ga. Laws 153-54 - (:unkn) unknown (My University, 1768)
Prohibited "any slave" from possessing firearms, ammunition, or weapons without a ticket from their master or a white person over the age of sixteen present and any time after sunset on Saturday but before sunrise Monday morning.
Keywords: ENSLAVED PERSONS & OTHER MINORITIES